PacBio genome sequencing reveals new insights into the genomic organisation of the multi-copy ToxB gene of the wheat fungal pathogen Pyrenophora tritici-repentis - Paula Moolhuijzen; Pao Theen See; Caroline S. Moffat (BMC Genomics, 2020)
Abstract Background Necrotrophic effector proteins secreted by fungal pathogens are important virulence factors that mediate the development of disease in wheat. Pyrenophora tritici-repentis (Ptr), the causal agent of wheat tan spot, has a race structure dependent on the combination of effectors. In Ptr, ToxA and ToxB are known proteinaceous effectors responsible for necrosis and chlorosis respectively. While Ptr ToxA is encoded by the single gene ToxA, ToxB has multiple loci in the Ptr genome, which is postulated to be directly related to the level of ToxB production and leaf chlorosis. Although previous analysis has indicated that the majority of the ToxB loci lie on a single chromosome, the exact number and chromosomal locations for all the ToxB loci have not been fully identified. Results In this study, we have sequenced the genome of a race 5 ToxB-producing isolate (DW5), using PacBio long read technology, and found that ToxB duplications are nested in the complex subtelomeric chromosomal regions. A total of ten identical ToxB gene copies were identified and based on flanking sequence identity, nine loci appeared associated with chromosome 10 and a single copy with chromosome 5. Chromosome 10 multiple ToxB gene loci were separated by large sequence regions between 31 and 66 kb within larger segmental duplications in an alternating pattern related to loci strand, and flanked by transposable elements. Conclusion This work provides for the first time the full accompaniment of ToxB loci and surrounding regions, and identifies the organization and distribution of ten ToxB loci to subtelomeric regions. To our knowledge, this is the first report of an interwoven strand-related duplication pattern event. This study further highlights the importance of resolving the highly complex distal chromosomal regions, that remain difficult to assemble, and can harbour important effectors and virulence factors.